A Novel Approach to Control Multi Terminal Direct Current Grids under Different Operation Conditions - SEDAGHATI Reza (Journal of Electrical and Electronics Engineering, 2023)
Frequency control plays a crucial role in maintaining stability and power equilibrium in Alternative Current (AC) systems, ensuring a balanced distribution between generation and demand. Similarly, in Direct Current (DC) systems, the stability of the grid depends on maintaining constant terminal voltages. Consequently, one of the primary responsibilities of High Voltage Direct Current (HVDC) stations is to uphold voltage stability across various operational modes. Thus, implementing an effective control strategy for DC voltage in a multi-terminal HVDC (MTDC) system becomes essential to achieve power equilibrium among interconnected nodes. A significant aspect to consider is how to distribute power among multi-stage transducers to maintain a balance between production and consumption while keeping the voltage constant. This paper proposes a novel approach that not only ensures balanced power sharing between the AC and DC networks but also maintains the DC voltage within an acceptable range and guarantees stability in the MTDC network during contingency analysis.